EFFECT OF FUNCTIONAL TRAINING ON ADOLESCENT HEALTH - Yang,Yang (2023)
ABSTRACT Introduction The high rate of obesity caused by the modern sedentary lifestyle associated with bad eating habits and the high intellectual demand at school generates a physical and psychological deficit in contemporary youth. The damage caused in this growth phase is irrecoverable, and the habits acquired during this period are crucial to individual health. The urgency of this problem has generated research on methods to reverse this situation, among them functional training. Objective To study the effect of functional training on adolescent health. Methods 30 boys and 30 girls were recruited as study subjects. The experiment lasted one semester, including two weekly physical education classes focused on functional training. Data on body indexes, fitness, and physical test results were collected before and after the intervention. The results of the experiment were integrated and compared. Results The selection of functional training can optimize adolescents’ biochemical indexes, making adolescents’ orthostatic posture more balanced, and significantly improve muscle strength, body flexibility, explosive strength of upper and lower extremities, motor coordination, body flexibility, muscular endurance, cardiopulmonary function, etc. Conclusion Functional training can effectively improve the physical health of adolescents. Participants have increased their interest in sports, and this intervention can potentially promote the development of adolescents’ physical and mental health if replicated nationwide. Studies are needed to popularize functional training in adolescents. Level of evidence II; Therapeutic studies - investigation of treatment outcomes.